Analysis of Regional Financial Performance of East Java Province - Taufiqqurrachman, Fahrizal; Yuvendo Arfiandy (Universitas Negeri Semarang, 2025)
East Java Province, as one of the regions with the largest economic and population contribution in Indonesia, plays a strategic role in realizing sustainable and inclusive regional development. In the context of regional autonomy that emphasizes accountability and efficiency of budget management, regional financial performance analysis is important to assess the extent to which provincial governments are able to manage fiscal resources independently, effectively, and sustainably. This study aims to find out the regional financial performance of East Java Province during the period 2016-2022. This study uses a quantitative research method with realized data from regional revenues, government transfer revenues, capital expenditures, regional expenditures, and regional original revenues from the Directorate General of Budget Balance Data Portal for 2016-2022. The ratio analysis method, namely a) fiscal decentralization, b) financial independence, c) financial dependence, d) efficiency and e) financial effectiveness, and f) regional financial compatibility was chosen because it was able to provide a comprehensive and multidimensional picture of the fiscal performance of East Java Province within the framework of regional autonomy, as well as reveal the strengths, weaknesses, and sustainability of its financial management. This approach is relevant for assessing not only the size of the budget but also the quality, impact, and long-term fiscal resilience. The results of fiscal decentralization showed a very good category, financial independence showed a high category with a pattern of delegative relationships, financial dependence showed a high category, financial effectiveness showed a very effective category, and financial efficiency showed a less efficient category. In the harmony of regional expenditure, it is divided into 2. First, the capital expenditure ratio shows a poor category. Second, the operating expenditure ratio shows a fairly good category. The findings of this study provide an empirical basis for local governments to develop fiscal policies that are more efficient, sustainable, and results-oriented, as well as an evaluation material in strengthening regional autonomy. At the academic level, the study enriches discussions about the relationship between fiscal decentralization and regional financial performance, particularly in the context of large provinces with complex fiscal burdens such as East Java.